A champion out of the pool? A discursive exploration of two Australian Olympic swimmers' transition from elite sport to retirement. (July 2015) - Cosh, Suzanne; Crabb, Shona; Tully, Phillip J.
Abstract: Background: The transition out of elite sport can be distressing and many athletes experience a range of transition difficulties. However, the socio-cultural and discursive contexts which shape experiences remain largely unexplored in the transition literature. Objective: To explore retirement and transition difficulties in a cultural context through an analysis of Australian newsprint media. Design and methods: A discursive analysis of 121 media articles reporting on post-retirement experiences of two Australian swimmers 7 and 5 years (respectively) into retirement. Data were analysed for repeated representation of transition difficulties, specifically how the cause of difficulties was attributed. The identities that were ascribed to athletes and what these functioned to accomplish were also examined. Results: The identities of both individuals were repeatedly constructed in terms of an athlete identity, to the exclusion of other identities. The responsibility for transition difficulties was depicted as located solely within the individual and, thereby, the sport setting and the broader socio-cultural context were overlooked. Conclusions: In this cultural context (Australian news media), the repeated construction of limited identity positions for retired athletes and the construction of former athletes as the sole locus of transition difficulties have implications for their psychological well-being. Despite this, the role of the sporting and cultural context is rendered invisible in these accounts and more broadly, and interventions remain targeted at the individual level. Highlights: Athlete identity is reproduced to the exclusion of other possible identities. A lack of alternate identities has implications for wellbeing into retirement. Responsibility for transition difficulties is located within the individual. Structural, organisational and socio-cultural factors are overlooked. Understanding transition difficulties requires consideration of the cultural context.